Influence of MP 29-02 on ciliary beat frequency in human epithelial cells in vitro - Häussler, Daniel; Sommer, Ulrich; Nastev, Alexander; Aderhold, Marc Christoph; Schell, Angela; Kramer, Benedikt; Stuck, Boris (European archives of oto-rhino-laryngology and head & neck, 2018)
MP 29-02, which contains fluticasone propionate and azelastine hydrochloride, is used as a topical nasal application for the treatment of seasonal and perennial allergic rhinitis. Although a multitude of data is available on the clinical symptom reduction and treatment safety of MP 29-02, the effect of MP 29-02 on ciliary beat frequency (CBF) has not been evaluated thus far.